2018
DOI: 10.1021/acs.langmuir.8b00662
|View full text |Cite
|
Sign up to set email alerts
|

Different Microtubule Structures Assembled by Kinesin Motors

Abstract: The microtubule-kinesin system is used to form microtubule-based structures via microtubule gliding motility. On the kinesin-coated surface, the microtubules can be easily assembled into stable micro- and nanostructures like circles and microtubule bundles using the streptavidin-biotin system. Furthermore, these microtubules structures can still retain performance with kinesin motor movement in spite of different velocities. Collisions bear responsibility for the majority of events leading to circle formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Our findings can be coupled with a vast array of bio-nanodevices that utilises MTs and MAPs (microtubule-associated proteins) for construction of bio-nanotransporters and bio-actuators [66][67][68][69][70]. Under specific conditions, MAP-MT systems are capable of repositioning macromolecules [71,72], directionally transporting microtubules [15,73] and even drive their movement within zero-mode waveguides [74] and inorganic nanotubes [75].…”
Section: Implications For the Cellmentioning
confidence: 89%
“…Our findings can be coupled with a vast array of bio-nanodevices that utilises MTs and MAPs (microtubule-associated proteins) for construction of bio-nanotransporters and bio-actuators [66][67][68][69][70]. Under specific conditions, MAP-MT systems are capable of repositioning macromolecules [71,72], directionally transporting microtubules [15,73] and even drive their movement within zero-mode waveguides [74] and inorganic nanotubes [75].…”
Section: Implications For the Cellmentioning
confidence: 89%
“…It has also been shown that microtubules can be modified by encapsulating artificial molecules. The use of motor proteins such as kinesins that walk in one direction on microtubules has also been devised [ 141 , 142 ]. This is used to transport objects and control the movement of microtubules.…”
Section: From Recent Examplesmentioning
confidence: 99%
“…Microtubules (MTs) are cytoskeletal components that serve important roles in various cellular processes, such as intracellular material transportation, cellular support, and cell division. MTs are hollow tubular structures consisting of tubulin heterodimers and are constantly extending (polymerizing) and contracting (depolymerizing) in cells. The dynamics of polymerization/depolymerization by MTs are essential to maintain cellular activities, including the cell cycle. Directional transport of intracellular cargos on MTs by motor proteins (kinesin and dynein) is also important in cells, which have been widely utilized to construct MT-based active materials. , Because of the importance of MTs, various methodologies have been developed to monitor MTs in living cells without chemical fixation to understand and modulate the dynamics of MTs. Expression of fluorescent protein-fused tubulin is a general method to monitor MTs in living cells . However, the low efficiency of transfection and low expression levels may be problematic.…”
Section: Introductionmentioning
confidence: 99%